Santri’s Humility in the Salafiyyah Islamic Boarding School - Azam Syukur Rahmatullah; Muhammad Azhar; Ahmad Fajruddin Fatwa (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
This research belongs to qualitative research, which explored the tawadhu' (humility) in the Lirboyo Islamic Boarding School, Kediri. Tawadhu' in Islamic boarding school is traditional, rooted, and has become a positive character. Thus, it deserves to be explored and later can be used as a